T61. EXAMINING THE RELATIONSHIP BETWEEN NEIGHBORHOOD CHARACTERISTICS AND PSYCHOSIS. (9th April 2019) - Orth, Ryan; Andrea, Alexandra; Savage, Christina; Bennett, Melanie; Blanchard, Jack
Abstract: Background: Neighborhood characteristics meaningfully influence mental health. Previous research has demonstrated relations between urbanicity and psychotic symptoms (Newbury et al, 2017; Zammit et al., 2010). There is also evidence to suggest that subjective ratings of neighborhood characteristics mediate this relation in adolescents (Newbury et al., 2017). The development of tools such as the Neighborhood Atlas (University of Wisconsin, 2018), which provides a composite measurement of overall neighborhood disadvantage in the form of Area Deprivation Index (ADI), and The Opportunity Atlas (Chetty et al., 2018), which provides specific neighborhood data such as incarceration rates and median neighborhood income statistics, offer a new opportunity to explore how objective neighborhood characteristics relate to mental health at a microneighborhood level. The current study seeks to explore the relation between objective and subjective neighborhood factors and psychotic symptoms. We hypothesize that 1) objective and subjective measurements of neighborhood factors will be significantly related, 2) beneficial subjective measurements (i.e., safety, social cohesion) will be negatively related to psychotic symptoms while detrimental subjective factors (i.e., violence) will be positively related to psychotic symptoms and 3) beneficial objective factors (i.e., median income) will be negatively related to psychotic symptoms, while detrimental objective factors (i.e., deprivation, incarceration) will be positively correlated with psychotic symptoms. Methods: Data were collected from a transdiagnostic sample of adults with psychotic disorders and healthy controls living in the Baltimore and Washington D.C. areas. Symptoms were measured using the Brief Psychiatric Rating Scale (BPRS). Subjective measures of neighborhood characteristics were assessed using the Neighborhood Environment Scale (NES), for which participants rate the area in a 1-mile radius around their home on several 4-point Likert subscales. Objective measures were gathered from Neighborhood Atlas, which provides a national percentile and state decile for ADI, and The Opportunity Atlas, which provided data on incarceration rates, median household income, and resident demographics, using participant addresses. Results: Preliminary analyses (N = 59) indicate only one significant relation between subjective and objective neighborhood measures with a relation between NES violence subscale and percentage of non-white residents (r = -.29, p = .031). There were no significant relationships between NES subscales and symptoms ratings. For objective neighborhood data, both state ADI decile and national ADI percentile were negatively correlated with BPRS positive symptoms (r = -.32, p = .019; r = -.32, p = .018) and agitation (r = -.32, p = .019; r = -.32, p = .016), indicating lower symptoms scores for those living in more deprived areas. State decile for ADI and incarceration rate were also negatively correlated with BPRS negative symptoms (r = -.29, p = .030; r = -.33, p = .034). Greater median household income was related with higher BPRS agitation scores (r = .28, p = .038). Discussion: Contrary to our hypotheses, results indicate that 1) objective and subjective neighborhood characteristics were largely unrelated, 2) self-reported neighborhood characteristics were unrelated to symptoms, and 3) beneficial objective factors such as median area income were positively correlated with symptoms while detrimental objective factors, such as ADI and incarceration rates, were negatively correlated with symptoms. One explanation for these findings may have to do with racial and diversity factors which will be further explored at the time of presentation.